Imidacloprid is hydroxylated by Laodelphax striatellus CYP6AY3v2. Issue 5 (27th June 2017) - Wang, R.; Zhu, Y.; Deng, L.; Zhang, H.; Wang, Q.; Yin, M.; Song, P.; Elzaki, M. E. A.; Han, Z.; Wu, M.
Abstract: Laodelphax striatellus (Fallén) is one of the most destructive pests of rice, and has developed high resistance to imidacloprid. Our previous work indicated a strong association between imidacloprid resistance and the overexpression of a cytochrome P450 gene CYP6AY3v2 in a L. striatellus imidacloprid resistant strain (Imid‐R). In this study, a transgenic Drosophila melanogaster line that overexpressed the L. striatellus CYP6AY3v2 gene was established and was found to confer increased levels of imidacloprid resistance. Furthermore, CYP6AY3v2 was co‐expressed with D. melanogaster cytochrome P450 reductase (CPR) in Spodoptera frugiperda 9 (SF9) cells. A carbon monoxide difference spectra analysis indicated that CYP6AY3v2 was expressed predominately in its cytochrome P450 (P450) form, which is indicative of a good‐quality functional enzyme. The recombinant CYP6AY3v2 protein efficiently catalysed the model substrate P‐nitroanisole to p‐nitrophenol with a maximum velocity ( V max ) of 60.78 ± 3.93 optical density (mOD)/min/mg protein. In addition, imidacloprid itself was metabolized by the recombinant CYP6AY3v2/nicotinamide adenine dinucleotide 2'‐phosphate reduced tetrasodium salt (NADPH) CPR microsomes in in vitro assays (catalytic constant ( K cat ) = 0.34 pmol/min/pmol P450, michaelis constant ( K m ) = 41.98 μM), and imidacloprid depletion and metabolite peak formation were with a time dependence. The data provided direct evidence that CYP6AY3v2 is capable of hydroxylation of imidacloprid and conferring metabolic resistance in L. striatellus .